All our trials : prisons, policing, and the feminist fight to end violence - Thuma, Emily L. (Women, gender, and sexuality in American history., 2019)
'All Our Trials' is a history of grassroots activism by, for, & about incarcerated domestic violence survivors, criminalized rape resisters, & dissident women prisoners in the 1970s & early 1980s. Across the country, in & outside of prisons, radical women participated in collective actions that insisted on the interconnections between interpersonal violence against women & the racial & gender violence of policing & imprisonment. These organizing efforts generated an anticarceral feminist politics that was defined by a critique of state violence; an understanding of race, gender, class, & sexuality as mutually constructed systems of power & meaning; & a practice of coalition-based organizing. Drawing on an array of archival sources as well as first-person narratives, the text traces the political activities, ideas, & influence of this activist current.